Micromanagement of Immune System: Role of miRNAs in Helminthic Infections - Arora, Naina; Tripathi, Shweta; Singh, Aloukick K.; Mondal, Prosenjit; Mishra, Amit; Prasad, Amit (Frontiers in Microbiology, 2017)
Helminthic infections fall under neglected tropical disease, although they inflict severe morbidity to human and causes major economic burden on health care system in many developing countries. There is increased effort to understand their immunopathology in recent days due to their immuno-modulatory capabilities. Immune response is primarily controlled at the transcriptional level, however microRNA-mediated RNA interference is emerging as important regulatory machinery that works at the translation level. In the past decade, microRNA (miRNA/miR) research has advanced with significant momentum. The result is ever increasing list of curated sequences from a broad panel of organisms including helminths. Several miRNAs had been discovered form trematodes, nematodes and cestodes like let-7, miR155, miR-199, miR-134, miR-223, miR-146 and fhe-mir-125a etc. with potential role in immune modulation. These miRs had been associated with TGF-β, MAPK, Toll-like receptor, PI3K/AKT signaling pathways and insulin growth factor regulation. Thus, controlling the immune cells development, survival, proliferation and death. Apart from micromanagement of immune system, they also express certain unique miRNA also like cis-miR-001, cis-miR-2, cis-miR-6, cis-miR-10, cis-miR-18, cis-miR-19, trs-mir-0001, fhe-miR-01, fhe-miR-07, fhe-miR-08, egr-miR-4988, egr-miR-4989 etc. The specific role played by most of these species specific unique miRs are yet to be discovered. However, these newly discovered miRNAs might serve as novel targets for therapeutic intervention or biomarkers for parasitic infections.